Reproductive Performance of Female Kacang Goats Supplemented by Mineral Under a Tethering Feeding System - Khalil Khalil; A. Bachtiar; Evitayani Evitayani (Tropical Animal Science Journal, 2019)
Inadequate feed intake and nutrient supply are associated with the suboptimal reproductive performance of Kacang goats reared using a traditional tethering system in the Pariaman region of Indonesia. The objectives of this study were to (i) identify reproductive problems in tethered female Kacang goats, (ii) assess crude nutrient and mineral composition of feed consumed by tethered goats, and (iii) evaluate the beneficial effects of mineral supplementation on reproductive performance of tethered female Kacang goats. A field survey was carried out in Pariaman City and the Padang Pariaman Regency to collect data on reproductive performance as well as blood mineral and hematological profiles of tethered female Kacang goats. Forage and feed samples were collected and analyzed for dry matter (DM), crude protein (CP), and minerals (Ca, P, Mg, Fe, Cu, and Zn) contents. Feed was formulated with supplemented complete minerals in either block form or mixed with feed. A total of 15 young female Kacang goats received feed without supplement (P0, n=5), or mineral supplement with feed (P1, n=5), or in a manually prepared block lick (P2, n=5). Parameters measured included body weight, number of pregnant goats, blood mineral concentrations, hematological parameters, total protein concentrations, and progesterone concentrations. Results of the field survey showed that the age of maturity of female Kacang goats reared under a tethering system ranged between 5 and 9 months and the first kidding occurred between 12 and 23 months. The suboptimal reproductive performance of female Kacang goats raised using a tethering system was closely related to the inadequate feed intake and nutritional deficiency. Supplementation with minerals is an effective method to enhance nutritional status and health to increase pregnancy rate of tethered female Kacang goats.